Can Women Shelters Help Reduce Symptoms of PTSD and C-PTSD? Trajectories of PTSD Symptom Development Following Partner- and Family-Related Violence - Dokkedahl, Sarah (Journal of interpersonal violence, 2022)
Background: To protect women from Intimate partner violence (IPV), women?s shelters should not only provide emergency safety from IPV exposure, but also prolonged support that empowers women to build a life free from violence. The present study aims to investigate individual symptom development in association with residency at a women?s shelter. Method: Data were collected at four different timepoints, that is, enrolment (T1, N = 150), 3-months residency (T2, = 110), 6-months residency (T3, N = 68) and after relocation (T4, N = 63). Women were included from four Danish women?s shelters. The International Trauma Questionnaire (ITQ) was applied to test for post-traumatic stress disorder (PTSD) and Complex-PTSD (C-PTSD) at all timepoints. A paired sample t-test was used to test the mean symptom development, and a Latent Class Growth Analysis (LCGA) was applied to test for different classes of PTSD-trajectories. Logistic regression was applied to predict class membership from shelter-related variables and symptom severity, that is, length of residency, psychological counselling, revictimization and key symptoms of C-PTSD. Results: The prevalence of PTSD (31%) and C-PTSD (37.9%) was high at enrolment. Although t-tests suggested a significant decline in symptoms at follow-up, the LCGA revealed different classes of symptom development. The two-class model was found to be the best representation of data with low-symptom- and high-symptom profiles, respectively. Overall, the largest decline in symptoms occurred within the first 3 months of residency. Revictimization was high and was further found to predict class membership. However, when included in a multiple regression only symptom severity predicted the high-symptoms profile class. Discussion: Psychological treatment focussing on PTSD and C-PTSD is important for the women?s future well-being and safety. Reports on revictimization was alarmingly high, which emphasises a continuing need to protect women from psychological violence within the shelters. These findings should be replicated in larger samples before we can draw any conclusion.